THE EFFECT OF USING PICTIONARY GAME TO INCREASE THE STUDENTS’ VOCABULARY MASTERY OF THE SEVENTH GRADE AT SMPN 4 BANTAN - Siti Aminah; Wan Julia Mayasari (INOVISH JOURNAL, 2022)
Astract : The aim of the study was to find out the effect of using Pictionary game on the students’ vocabulary mastery before and after being taught by using this game. There were two classes as the samples namely experimented class with twenty (20) students and the other was controlled class with twenty (20) students as well. Three questions were formulated : a) How is the students’ vocabulary mastery before being taught by using Pictionary game?, b) How is the students’ vocabulary mastery after being taught by using Pictionary game?and c) Is there any significant effect on the students’ vaocabulary mastery by using Pictionary game?. Based on the result, the mean score of expermented class was 73, controlled class 60 and ttest was 4,00. It showed that ttest was higher than ttable in 1% and 5% (2.03≤4,00≥2.72). It meant that Ha was accepted and Ho was rejected. In sum, Pictionary game was effective to increase the students’ vocabulary mastery of the seventh grade at SMPN 4 Bantan. Key Words : Vocabulary, Pictionary Game.